The Economic–Social Performance Relationships of Ports: Roles of Stakeholders and Organizational Tension. (31st March 2016) - Cheon, SangHyun
Abstract: This study examines the mechanisms that shape relationships between port economic and social performance. Based on the concepts of organizational paradox and stakeholder heterogeneity, the study develops a paradox–stakeholder combination matrix to explain context‐ and issue‐specific economic–social performance relationships. Differing economic–social performance links may vary with different stakeholders' roles in relation to ports' sustainable development issues. The empirical evidence from US ports provides crucial implications for quasi‐public organizations, which face complex organizational identities. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment